A Lexical-Semantic and Linguo-Cultural Study of Computer Terminology in English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides a concise overview of a study exploring computer terminology in English and Uzbek languages. It highlights the lexical-sematic and linguo-cultural dimensions of this specialized vocabulary, examining how technological concepts are expressed and understood in different linguistic and cultural contexts. By shedding light on the evolution, adaptation, and cross-cultural communication challenges of computer terminology, the study offers valuable insights into the intersection of language, technology, and culture.